[Afisz. Incipit:] Państwowy Teatr "Wybrzeże" Repertuar 16-22.05.1949. (Gdańsk : [wydawca nieznany], 1949)
Afisz z repertuarem na 16-22.05.1949 r.
Keywords: Teatr Wybrzeże (Gdańsk) -- 1945-1970 -- druki ulotne